2015
DOI: 10.4103/2153-3539.166013
|View full text |Cite
|
Sign up to set email alerts
|

Working toward consensus among professionals in the identification of classical cervical cytomorphological characteristics in whole slide images

Abstract: Introduction:Cervical cancer is one of the most common causes of death in women worldwide.[1] The introduction of cervical cytology in screening programs is an effective way for early detection and treatment of cervical precancerous lesions. Conventional screening of cervical cytology slides is still considered the current “gold standard” for the assessment of proficiency in becoming a cytotechnician, but diagnosis using digital whole slide images (WSI) may offer many advantages.Materials and Methods:In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Furthermore, we are currently exploring ways of integrating in‐house‐developed deep‐learning algorithms and Visiopharm image‐processing algorithms for routine diagnostic work in order to determine how effective they would be in practice. Finally, we have started working on the implementation of Z‐scanning for cytology . When Z‐stacks appear to be necessary, this will have consequences for our scanning and storage workflow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we are currently exploring ways of integrating in‐house‐developed deep‐learning algorithms and Visiopharm image‐processing algorithms for routine diagnostic work in order to determine how effective they would be in practice. Finally, we have started working on the implementation of Z‐scanning for cytology . When Z‐stacks appear to be necessary, this will have consequences for our scanning and storage workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have started working on the implementation of Zscanning for cytology. 22,23 When Z-stacks appear to be necessary, this will have consequences for our scanning and storage workflow.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Bongaerts et al found that in cervical LBC, the observers found a distance of 2 μm between the z‐dimension layers and seven levels more acceptable than a 1 μm distance. Earlier, Mori et al in a complex study based on cells dimensions determined that “layers of 1.5 μm thickness each with a total of 10 to 15 layers resulting in 15 to 20 μm scan is suitable for most cytology slides”.…”
Section: Z‐stack Levelsmentioning
confidence: 99%
“…Despite meticulous scanning of a sample, certain features such as granules, small inclusion bodies and small pathogens are not necessarily obvious on scanned slides (personal observation). In such instances, the pathologist needs to go back to the actual glass slide or request reimaging of the glass slide by alternative modalities, such as Z‐stack images …”
Section: Digital Microscopymentioning
confidence: 99%
“…In such instances, the pathologist needs to go back to the actual glass slide or request reimaging of the glass slide by alternative modalities, such as Z-stack images. 6…”
Section: Disadvantages and Challengesmentioning
confidence: 99%